TRPC channels blockade abolishes endotoxemic cardiac dysfunction by hampering intracellular inflammation and Ca2+ leakage - Na Tang; Wen Tian; Guang-Yuan Ma; Xiong Xiao; Lei Zhou; Ze-Zhi Li; Xiao-Xiao Liu; Chong-Yao Li; Ke-Han Wu; Wenjuan Liu; Xue-Ying Wang; Yuan-Yuan Gao; et al. (Nature Communications, 2022)
TRPCs, nonselective cation channels, are involved in cardiac contraction and conduction. Here, the authors show that Trpc1/6 deficiency or pharmacological inhibition improves endotoxemic cardiac dysfunction and prolongs survival by prominently suppressing cardiac inflammation and ER Ca2+ release.